Inflammatory Response of THP1 and U937 Cells: The RNAseq Approach - Layla Panahipour; Chiara Micucci; Reinhard Gruber (Cells)
THP1 and U937 are monocytic cell lines that are common bioassays to reflect monocyte and macrophage activities in inflammation research. However, THP-1 is a human monocytic leukemia cell line, and U937 originates from pleural effusion of histiocytic lymphoma; thus, even though they serve as bioassay in inflammation research, their response to agonists is not identical. Consequently, there has yet to be a consensus about the panel of strongly regulated genes in THP1 and U937 cells representing the inflammatory response to LPS and IFNG. Therefore, we have performed an RNAseq of THP1 and U937 exposed to LPS and IFNG to identify the most sensitive genes and the unique properties of each individual cell line. When applying a highly stringent threshold, we could identify 43, 8 up and 94, 103 down-regulated genes in THP1 and U937 cells, respectively. In THP1 cells, among the most strongly up-regulated genes are CCL1, CXCL2, CXCL3, IL1A, IL1B, IL6, and PTGES. In U937 cells, the strongest up-regulated genes include CSF2, CSF3, CXCL2, CXCL5, CXCL6, IL1A, IL19, IL36G, IL6, ITGA1, ITGA2, and PTGS2. Even though THP1 is considerably less responsive than U937, there are genes commonly upregulated by LPS and IFNG, including the CCL1, CCL3, CCL20, CXCL2, CXCL3, CXCL8, as well as IL1A, IL1B, IL23A, IL6, and genes of prostaglandin synthesis PTGES and PTGS2. Downregulated genes are limited to NRGN and CD36. This head-to-head comparison revealed that THP1 is less responsive than U937 cells to LPS and IFNG and identified a panel of highly regulated genes that can be applied in bioassays in inflammation research. Our data further propose bulk RNAseq as a standard method in bioassay research.